Vis a Vis: Beyond the Veil - Lawrence, Steven; Spencer, Kim (United States, 1998)
English literature teachers, Deborah Whitley of Washington, D.C., and Sima Daad of Tehran, engage in discussion through a digital video link. In conversations taking place over four days, they confront many of the social and political differences that have kept their countries at odds with one another, including the hijab (the veil) and the fatwa (death sentence).
Soros Documentary Fund
Keywords: United States